2019
DOI: 10.21608/ejh.2019.13126.1127
|View full text |Cite
|
Sign up to set email alerts
|

Histological study of the effect of tributyltin on the adrenal cortical cells of adult male albino rats.

Abstract: Background:Tributyltin is widely used as antifouling paint for marine vessels. It is slowly released from the paint to the water and becomes incorporated into soil, animals and plants. TBT has been identified as an endocrine disruptor and induces oxidative damage. Objectives: This study aimed to investigate the probable toxic effect of tributyltin on adrenal cortical cells of adult male albino rats for two different durations. Materials and Methods: Twenty four adult male albino rats were divided into 3 equal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Similar observations were noted by Solaiman and Sawires (2019) who studied the impact of tributyltin on the suprarenal cortex, and they owed these results to the endocrine-disrupting effect of it that caused impaired steroidogenesis.…”
Section: Ii-morphometric Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Similar observations were noted by Solaiman and Sawires (2019) who studied the impact of tributyltin on the suprarenal cortex, and they owed these results to the endocrine-disrupting effect of it that caused impaired steroidogenesis.…”
Section: Ii-morphometric Resultssupporting
confidence: 77%
“…The present work revealed that H&E staining showed disturbed arrangements of cells in the zona glomerulosa and the zona fasciculata with many of them had darkly stained nuclei. Similar observations were confirmed in the suprarenal cortex of rats exposed to the endocrine disruptor tributyltin (Solaiman and Sawires 2019). El-Shenawy (2009) studied the oxidative stress response of Roundup and glyphosate and assumed that Roundup, by reducing the level of GSH, led to an oxidative imbalance, resulting in cell death.…”
Section: Ii-morphometric Resultsmentioning
confidence: 75%
“…In our study, the increased levels of ACTH recorded in sera of CPZ-intoxicated rats confirmed that the reduction in cortisol level may be attributed to the direct effect of CPZ on the steroidogenesis. Solaiman and Seddik (22) got similar findings after treating rats with 1 mg Tributyltin, antifouling paint, dissolved in 0.4 mL corn oil once daily via a gastric tube for one week. Choi et al (23) revealed that azole compounds, such as ketoconazole and the fungicide fenarimol, inhibit various CYP450 isoforms and, as a result, can influence steroid synthesis.…”
Section: Discussionmentioning
confidence: 64%
“…BDE3 up-regulates Cyp11b1 expression and causes AMPK signaling disruption by decreasing its phosphorylation in rats exposed to 200mg/kg of BDE3 ( 176 ). TBT is an oxidative endocrine disrupter, which increases intracellular storage ( 177 ) and causes the accumulation of lipids and cholesterol in adrenal cells, which results in weakened cholesterol utilization and increased cholesterol levels ( 178 ). Organophosphates like isopropylated triphenyl phosphate [IPTPP] cause hypertrophy of the adrenal cortical in zona fasciculate and increase the relative weight of the adrenal gland ( 156 ).…”
Section: Effects Of Mps Nps and Their Associated Chemicals On The Adr...mentioning
confidence: 99%